2017
DOI: 10.3390/nano7090255
|View full text |Cite
|
Sign up to set email alerts
|

Hollow Au–Ag Alloy Nanorices and Their Optical Properties

Abstract: Hollow noble metal nanoparticles have excellent performance not only in surface catalysis but also in optics. In this work, the hollow Au–Ag alloy nanorices are fabricated by the galvanic replacement reaction. The dark-field spectrum points out that there is a big difference in the optical properties between the pure Ag nanorices and the hollow alloy nanorices that exhibit highly tunable localized surface plasmon resonances (LSPR) and that possess larger radiative damping, which is also indicated by the finite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 37 publications
0
7
0
1
Order By: Relevance
“…Therefore, we can match the obtained dark field scattering spectrum with its corresponding AuNC@J-agg individual, and the scattering spectrum and SEM image for points A and B are presented in Figure 3biii),ciii), respectively. These dark field measurements have been extensively used in the study of single nanoparticle systems (including our group) [14,21,22,36,37,38], demonstrating high reliability and stability. In our dark field measurements, close-packed AuNC@J-agg hybrids were also collected (Figure 3d).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we can match the obtained dark field scattering spectrum with its corresponding AuNC@J-agg individual, and the scattering spectrum and SEM image for points A and B are presented in Figure 3biii),ciii), respectively. These dark field measurements have been extensively used in the study of single nanoparticle systems (including our group) [14,21,22,36,37,38], demonstrating high reliability and stability. In our dark field measurements, close-packed AuNC@J-agg hybrids were also collected (Figure 3d).…”
Section: Resultsmentioning
confidence: 99%
“…Silver or gold nanorice structures support both transverse and longitudinal resonances, with the latter tunable from the visible to the near-infrared spectral range by variation of the aspect ratio (length/diameter) 26 , 27 . With increasing aspect ratio of nanorice, higher-order multipolar LSPR modes can be excited 28 , 29 , which facilitates their applications in ultrasensitive sensing 28 , surface-enhanced Raman spectroscopy 29 , and catalysis 30 . These current studies of silver or gold nanorices won’t pay attention to multi-resonance phenomenon with the spatial overlap of the electric hotspots for surface enhancement hyper-Raman scattering.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, AuCl − 4 ions will preferentially react with Ag atoms on the {111} plane. Owing to the Kirkendall effect [46,49], Ag-Au bimetallic nanoprisms with numerous nanometer size protrusions and pores can be obtained, that is, roughened nanoporous Ag-Au bimetallic TNPs, as shown in Figure 1(c). It is interesting to know that the average particle size of TNPs is almost unaffected before (~284 nm) and after (~289 nm) the galvanic displacement (see Figure S2), which also confirmed that the formations of nanoporous Ag-Au alloyed nanoprisms are based on the galvanic displacement by using the Ag nanoprisms as a frame.…”
Section: Resultsmentioning
confidence: 99%